Hepatoprotective effects of naturally fermented noni juice against thioacetamide‐induced liver fibrosis in rats. Issue 4 (April 2017) - Lin, Yi‐Ling; Lin, Hui‐Wen; Chen, Yi‐Chen; Yang, Deng‐Jye; Li, Chien‐Chun; Chang, Yuan‐Yen
Abstract : Background : Excessive reactive oxygen species (ROS) can result in inflammation and cytokine secretion in the liver, and then activate hepatic stellate cells that cause the accumulation of extracellular matrix proteins, especially collagen, in liver tissue. Naturally fermented noni juice (NJ; Morinda citrifolia ) has been used for decades as a nutraceutical in humans. In this study, we intended to examine if NJ can ameliorate ROS‐induced liver fibrosis via a thioacetamide (TAA)‐induced rat model. Methods : The 50 rats used in this study were separated into five groups of 10 rats each for 8 weeks as follows: (1) control group; (2) TAA; (3) TAA + low‐dose NJ (2.51 mL NJ/kg); (4) TAA + medium‐dose NJ (5.02 mL NJ/kg); and (5) TAA + high‐dose NJ (7.52 mL NJ/kg). Results : Treatment with TAA resulted in lower body weight and serum lipid levels ( p < 0.05), while liver weight and collagen contents, and serum alanine aminotransferase and aspartate aminotransferase values were increased ( p < 0.05). The protective effects of NJ on TAA treatment resulted from decreased endoplasmic reticulum stress‐related gene expressions ( p < 0.05), inflammatory cytokines, collagen accumulation, and matrix metalloproteinase (MMP‐2 and MMP‐9) activities, as well as upregulated ( p < 0.05) tissue inhibitors of metalloproteinase (TIMP‐1 and TIMP‐3) in livers. NJ also increased hepatic antioxidant capacities ( p < 0.05). Conclusion : Naturally fermented NJ manifests a protective potential on liver fibrosis via the enhancement of antioxidant capacities, as well as decreasing endoplasmic‐reticulum stress and MMP‐2/MMP‐9 activities.